Comparison of Field-of-view Optimized and Constrained Undistorted Single Shot With Conventional Intravoxel Incoherent Motion Diffusion-Weighted Imaging for Measurements of Diffusion and Perfusion in Vertebral Bone Marrow. Issue 1 (January 2021) - Cao, Jibin; Zhu, Jingyi; Sun, Wenge; Cui, Lingling
Abstract : Background and Purpose: A limited number of studies have used the intravoxel incoherent motion (IVIM) diffusion-weighted imaging (DWI) approach on bone marrow. The purpose of this study was to qualitatively and quantitatively compare the clinical value of IVIM based on field-of-view optimized and constrained undistorted single shot (FOCUS) with the standard single-shot echo-planar imaging (ss-EPI) in the vertebral bone marrow. Materials and Methods: Twenty healthy volunteers underwent ss-EPI and FOCUS IVIM-DWI of the lumbar spine. Intravoxel incoherent motion parameters (the apparent diffusion coefficient [ADC], true diffusion coefficient [ D ], pseudodiffusion coefficient [ D *], and perfusion fraction [ f ]) were calculated. Results: The FOCUS IVIM protocol allowed for measurement of ADC, D, D *, and f in all volunteers: ADC, 0.28 ± 1.33 ×10 −3 mm 2 /s; D = 0.25 ± 3.98 ×10 −3 mm 2 /s, f = 0.36 ± 4.01; and D * = 102.16 ± 71.21 ×10 −3 mm 2 /s. There were no significant differences between the values of ADC, D, and f obtained with ss-EPI and FOCUS. The D * was significantly different ( P < 0.05) between ss-EPI and FOCUS IVIM. Image quality assessments showed that the image qualities of FOCUS were superior to ss-EPI ( P < 0.001). Conclusions: As a high-resolution IVIM-DWI technique, the FOCUS technique has potential clinical utility in evaluating the diffusion and perfusion in the vertebral bone marrow.